CAPITAL STRUCTURE ANALYSIS OF THE COMPANY: EMPIRICAL EVIDENCE IN THE RETAIL TRADE SECTOR IN INDONESIA STOCK EXCHANGE - Oriza Herlina Amalia; Dhani Ichsanuddin Nur (Universitas Kuningan, 2019)
The funding policy is one thing that must be considered by the company because it is related to many parties such as creditors, shareholders and company management. The funding policy is closely related to determining the proportion of debt and capital of a company, known as capital structure. Many factors can affect a company's capital structure. Therefore, the purpose of this research is to find out and analyze the effect of profitability, business risk, asset structure and sales growth as factors considered by the company towards capital structure decision making of retail trade sub-sectors listed on the Indonesia Stock Exchange period 2015-2018 . The population used in this study is the retail trade sub-sector companies listed on the Indonesia Stock Exchange totaling 26 companies. The sampling method in this study was purposive sampling with the sample in this study were 16 companies. The method used in this research is multiple linear regression analysis. The results of this study indicate that the independent variables, namely profitability, business risk and sales growth can contribute in determining the capital structure of retail trade sub sector companies. While the asset structure cannot contribute to the determination of the capital structure of the retail trade sub sector company.